Performance Comparison of Ground Source Heat Pump (GSHP) against Air Source Heat Pump (ASHP) for Domestic Applications: A case study in Perth, Australia - Aprianti, Tine; Tan, Evan; Diu, Chan; Sprivulis, Ben; Ryan, Greg; Srinivasan, Kandadai; Chua, Hui Tong (Teknomekanik, 2021)
The goal of this research is to evaluate the efficacy and practicality of installing a ground source heat pump (GSHP) with an air source heat pump (ASHP) in a residential setting. The results of this comparison were obtained by monitoring each of the systems in two almost identical residences in Perth, Western Australia. There is an open-loop groundwater system in the previous home. Each residence has one family whose air conditioning system has its own set of operational needs. The cooling capacity supplied and coefficient of performance (COP) as a function of seasonal changes in ambient temperatures were determined using data gathered from both residences over a two-year period. For both heating and cooling, the GSHP system COP was found to be greater than that of the ASHP system. Furthermore, these two performance measures were independent of ambient circumstances in the former, but they exhibit a noticeable ambient dependent trend in the latter. The GSHP had an average COP of 4.0 for heating, regardless of external conditions, while the ASHP COP ranged from 2.0 to 3.0. Conversely, the GSHP had an average COP of 3.2 for cooling, whereas the ASHP COP ranged from 1.4 to 2.9. It is found that GSHPs result in significant operational cost reductions and a significant decrease in greenhouse gas emissions when a borewell is part of a home.